2014
DOI: 10.1371/journal.pone.0097692
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Axonal Arborization and Synaptic Bouton Formation Critically Rely on Abp1 and the Arp2/3 Complex

Abstract: Neuronal network formation depends on properly timed and localized generation of presynaptic as well as postsynaptic structures. Although of utmost importance for understanding development and plasticity of the nervous system and neurodegenerative diseases, the molecular mechanisms that ensure the fine-control needed for coordinated establishment of pre- and postsynapses are still largely unknown. We show that the F-actin-binding protein Abp1 is prominently expressed in the Drosophila nervous system and reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…Functional genomic tests revealed enrichment in association to starvation resistance among genes categories annotated in actin filament production (Additional file 1: Table S5). In the latter, top-scoring genes were Arp2 , Arpc2 , and SCAR (association p  = 0.0008, 0.001, and 0.003 respectively), which have roles in the development of neural processes and axonal defasciculation [52, 53]. Also emerging from functional genomic tests was an enrichment in association to starvation resistance among heterophilic cell-cell adhesion genes (Additional file 1: Table S5); these included Notch (association p  = 0.006), among whose many biological roles is that of axon guidance [54], and “beaten path” genes such as beat - Ib , beat - IIIb , and beat - Va (association p  = 0.00001, p  = 0.00008, p  = 0.0002 respectively), which are involved in motor neuron defasciculation [55].…”
Section: Resultsmentioning
confidence: 99%
“…Functional genomic tests revealed enrichment in association to starvation resistance among genes categories annotated in actin filament production (Additional file 1: Table S5). In the latter, top-scoring genes were Arp2 , Arpc2 , and SCAR (association p  = 0.0008, 0.001, and 0.003 respectively), which have roles in the development of neural processes and axonal defasciculation [52, 53]. Also emerging from functional genomic tests was an enrichment in association to starvation resistance among heterophilic cell-cell adhesion genes (Additional file 1: Table S5); these included Notch (association p  = 0.006), among whose many biological roles is that of axon guidance [54], and “beaten path” genes such as beat - Ib , beat - IIIb , and beat - Va (association p  = 0.00001, p  = 0.00008, p  = 0.0002 respectively), which are involved in motor neuron defasciculation [55].…”
Section: Resultsmentioning
confidence: 99%
“…Imp encodes an mRNA binding protein that promotes and regulates transcript targeting, and plays a role in axonal remodeling, synaptogenesis and oogenesis (BOYLAN et al 2008;MEDIONI et al 2014). Arp3 encodes an actin related protein that is required for myoblast fusion and axonal arborization and synapse formation (RICHARDSON et al 2007;KOCH et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ena prevents Arp2/3-induced branching (Bear and Gertler, 2009), suggesting that Ena inactivation activates Arp2/3 and results in satellite bouton formation, similar to Rac activation (Ball et al, 2010) or to loss of SCAR/WAVE components (Ball et al, 2010; Qurashi et al, 2007; Schenck et al, 2004; Zhao et al, 2013). It is reported that Arp2/3 is involved in bouton formation and axon terminal branching downstream of WAVE/SCAR complex in NMJ (Koch et al, 2014). Indeed, our findings support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the many factors, elements of the actin cytoskeleton are key effectors of morphological change, functioning downstream of several cell surface receptors and signaling pathways (Long and Van Vactor, 2013). Of the two types of actin filaments (branched and linear), the activity of Arp2/3 complex, responsible for nucleation of branched F-actin, the first step of actin polymerization (Insall and Machesky, 2009), should be strictly regulated (Koch et al, 2014). Arp2/3 hyperactivation results in synaptic terminal overgrowth characterized by excess small boutons emanating from the main branch (Ball et al, 2010; Qurashi et al, 2007; Schenck et al, 2004; Zhao et al, 2013) that are termed satellite boutons (Dickman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%